Victor McKusick and the history of medical genetics - Francomano, Clair A.; Dronamraju, Krishna R. (Springer New York, 2012)
Victor McKusick is widely known as the 'Founding Father of Medical Genetics'. His seminal contributions to all aspects of medical genetics have led to the establishment of a distinct discipline. As a clinician, teacher, scientist, historian and author, McKusick's role is unparalleled. He was a founding member and the first President of the Human Genome Organization (HUGO). He performed an outstanding service by bringing genetics into the mainstream of medicine. This book is a tribute to Victor McKusick and the field of Medical genetics that he pioneered.  It contains a number of fascinating personal accounts of people who knew, worked, and were influenced by him in the period from around 1950 until his death in 2007.  Through this mechanism, the reader is given a unique insight into the history of medical genetics and how it will impact 21st century medicine.                                                            -- Dr. Hamilton O. Smith, Nobel Laureate